Soil properties drive population abundance of the rare, endemic Euphorbia yaroslavii in the Zailiyskiy Alatau, Kazakhstan - ZHANSAYA ТURGARA; ABIBULLA AMETOV; KANAT KULYMBET; ASSEL CHILDIBAYEVA; SALTANAT NAZARBEKOVA; TOLGANAY RYSKALI; ULZHAN EREZHETOVA; ASEM TASTANBEKOVA (Society for Indonesian Biodiversity, 2025)
Abstract. ?urgara Z, Ametov A, Kulymbet K, Childibayeva A, Nazarbekova S, Ryskali T, Erezhetova U, Tastanbekova A. 2025. Soil properties drive population abundance of the rare, endemic Euphorbia yaroslavii in the Zailiyskiy Alatau, Kazakhstan. Biodiversitas 26: 5881-5890. This study investigates the ecological and soil-chemical factors influencing the population abundance of the rare herbaceous perennial geophyte Euphorbia yaroslavii in the Zailiyskiy Alatau Mountains, Southeastern Kazakhstan. Field surveys were conducted across three gorges - Ushkonyr, Shamalgan, and Kaskelen - comprising nine cenopopulations. A total of 337 individuals were recorded, with the highest abundance observed in Ushkonyr (188 individuals) and the lowest in Kaskelen (56 individuals). Soil texture, structure, and chemistry were analyzed in detail, including granulometry, humus content, pH, CO?, available N, P?O?, K?O, exchangeable cations (Ca²?, Mg²?, Na?, K?), and total soluble salts. Pearson correlation analysis revealed very strong positive correlations between population abundance and sand (r = +0.95), clay (r = +0.87), humus (r = +0.80), mobile nitrogen (r = +0.93), and with exchangeable magnesium among key base cations (r = +0.92). A strong negative correlation was found with silt content (r = -0.88), indicating that excess silt may limit aeration. Correlations were computed at the cenopopulation level (n = 9), pairing abundance with co-located soil measurements from the 0-20 cm layer. The most favorable soil conditions for E. yaroslavii are loamy calcareous soils with 40-50% sand, 20-30% clay, slightly alkaline pH (7.4-7.9), humus ? 2.5%, and high base saturation with dominance of Ca²? and Mg²?. These findings suggest that population abundance is primarily determined by soil texture and organic matter, with magnesium acting as an important component of an overall balanced base-cation regime. Sites meeting these criteria should be prioritized for in situ conservation and habitat restoration, with recommended practices including organic amendment and liming to improve soil fertility and structure.